In Situ Formation of Protective Coatings on Sulfur Cathodes in Lithium Batteries with LiFSI-Based Organic Electrolytes - Kim, Hyea; Wu, Feixiang; Lee, Jung Tae; Nitta, Naoki; Lin, Huan-Ting; Oschatz, Martin; Cho, Won Il; Kaskel, Stefan; Borodin, Oleg; Yushin, Gleb (WILEY-V C H VERLAG GMBH, 2015)
Development of sulfur cathodes with 100% coulombic efficiency (CE) and good cycle stability remains challenging due to the polysulfide dissolution in electrolytes. Here, it is demonstrated that electrochemical reduction of lithium bis(fluorosulfonyl)imide (LiFSI) based electrolytes at a potential close to the sulfur cathode operation forms in situ protective coating on both cathode and anode surfaces. Quantum chemistry studies suggest the coating formation is initiated by the FSI(-F) anion radicals generated during electrolyte reduction. Such a reduction additionally results in the formation of LiF. Accelerated cycle stability tests at 60 degrees C in a very simple electrolyte (LiFSI in dimethoxyethane with no additives) show an average CE approaching 100.0% over 1000 cycles with a capacity decay less than 0.013% per cycle after stabilization. Such a remarkable performance suggests a great promise of both an in situ formation of protective solid electrolyte coatings to avoid unwanted side reactions and the use of a LiFSI salt for this purpose.
Keywords: CARBON; PERFORMANCE; CELLS; SALT; TEMPERATURE; PARTICLES; STABILITY; CAPACITY; LIQUID